Declaration of Commitment of Port of Spain ([Government of Trinidad and Tobago] [Port of Spain]TT, 2009)
Deals with the Heads of State and Governments' commitment to promoting human prosperity, energy security, environmental sustainability, to strengthening public security, democratic governance and also strengthening the Summit of Americas follow-up and implementation effectiveness.
Keywords: WEALTH